KESALAHAN EJAAN PADA LATAR BELAKANG SKRIPSI MAHASISWA PBSI UNIVERSITAS MUHADI SETIABUDI TAHUN 2023 - Putriyanasari; Budiana, Nurchalistiani; Kurniawan, Prasetyo Yuli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the forms and impacts of spelling errors in the background of thesis of students of the Indonesian Language and Literature Education Study Program (PBSI) Muhadi Setiabudi University in 2023. Using a descriptive qualitative approach with a content analysis method, data were collected through documentation of the background of the students' theses. The results of the analysis showed a total of 272 cases of spelling errors, including 95 letter usage errors, 68 word spelling errors, 72 punctuation errors, 1 loan element spelling error, and 36 typos. The most frequently found errors were the incorrect use of capital letters, the writing of combined prepositions, and inaccuracy in the use of punctuation according to the Enhanced Spelling (EYD) Edition V. The impact of these spelling errors is very significant, including obscuring meaning, reducing the academic quality of scientific work, hindering the effectiveness of scientific communication, complicating the assessment process by the supervisor, and indicating a lack of student understanding of correct Indonesian language rules. These findings underscore the need for improved understanding of EYD Edition V, accuracy in writing, and more intensive guidance from supervisors to improve the quality of students' scientific writing. This research is expected to serve as a reference for students and educational institutions in efforts to improve language literacy and academic standards.